2012
DOI: 10.1186/1479-5876-10-160
|View full text |Cite
|
Sign up to set email alerts
|

Low density lipoprotein receptor-related protein 1 expression correlates with cholesteryl ester accumulation in the myocardium of ischemic cardiomyopathy patients

Abstract: Our hypothesis was that overexpression of certain lipoprotein receptors might be related to lipid accumulation in the human ischemic myocardium. Intramyocardial lipid overload contributes to contractile dysfunction and arrhythmias in cardiomyopathy. Thus, the purpose of this study was to assess the effect of hypercholesterolemic LDL and hypertrigliceridemic VLDL dose on LRP1 expression in cardiomyocytes, as well as the potential correlation between LRP1 expression and neutral lipid accumulation in the left ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 34 publications
1
31
0
Order By: Relevance
“…Our group reported that LRP1 is upregulated at transcriptional level by hypercholesterolemia through sterol regulatory element-binding proteins (SREBP) downregulation in human VSMC, [8][9][10] and by hypoxia through hypoxia-inducible factor 1α upregulation in human VSMC 11 and cardiomyocytes. 12,13 Other groups have reported that insulin promotes the presence of LRP1 in the plasma membrane without influencing mRNA expression levels. 14,15 LRP1 cellular turnover is regulated by the ubiquitinproteasome system, 16 an important mechanism for targeting membrane proteins to destruction, and therefore key in the modulation of protein levels.…”
mentioning
confidence: 99%
“…Our group reported that LRP1 is upregulated at transcriptional level by hypercholesterolemia through sterol regulatory element-binding proteins (SREBP) downregulation in human VSMC, [8][9][10] and by hypoxia through hypoxia-inducible factor 1α upregulation in human VSMC 11 and cardiomyocytes. 12,13 Other groups have reported that insulin promotes the presence of LRP1 in the plasma membrane without influencing mRNA expression levels. 14,15 LRP1 cellular turnover is regulated by the ubiquitinproteasome system, 16 an important mechanism for targeting membrane proteins to destruction, and therefore key in the modulation of protein levels.…”
mentioning
confidence: 99%
“…However, there are no data indicating a role for LRP1 in cardiac lipid metabolism under normal conditions. Treatment of isolated cardiomyocytes with increasing doses of LDL and VLDL in normoxic conditions led to increased levels of VLDLr and LRP1 expression, while LDLr expression did not change [ 82 ]. When LRP1 was knocked down in isolated cardiomyocytes that were treated with LDL, cholesteryl ester uptake continued although at a signifi cantly slower rate [ 82 ].…”
Section: Cardiac Lipoprotein Receptorsmentioning
confidence: 94%
“…This may involve the VLDLr [ 74 ], although changes in cardiac lipid uptake and accumulation during ischemia might be model specifi c. In one report, myocardial infarction in mice led to a marked increase in expression of VLDLr and accumulation of intracellular lipids; this was prevented by with VLDLr defi ciency [ 74 ]. Increased VLDLr expression levels due to ischemia may be driven by hypoxia-inducible factor (HIF)-1α, which is elevated in ischemic hearts [ 82 ] and is a positive regulator of VLDLr expression [ 74 , 117 ]. However, in rat models of low-fl ow ischemia cardiac FA uptake and TG content were reduced [ 118 ].…”
Section: Ischemiamentioning
confidence: 95%
See 2 more Smart Citations